Practical learning and professional development of preschool teachers: the role of practicum - Lino, Dalila (2020)
Nowadays is recognized that practicum has a key role in the initial education of teachers and preschool teachers, being considered as a fundamental axis for the professional development of these professionals. It is acknowledged that this period of supervised, reflected and experiential learning acts as a wedge between the academic and theoretical training and the one that occurs in practice contexts, being practicum pointed out by research as a crucial space and time to promote the preschool teachers’ awareness of the profession and the acquisition of human skills and qualities of practical thinking and professional knowledge. This study is part of a research project that aims to understand the role of practicum for preschool and 1st and 2nd cycle of basic education teachers.